A Method of Velocity Curve Calculation for Train Based on Accurate Running Time - TIAN Changyu; LIU Jiazheng; ZHANG Chao (Kongzhi Yu Xinxi Jishu)
In order to improve the accuracy of train running time between stations in automatic train operation (ATO) mode, and also to make it be possible to adjust the plan based on interval time for automatic train supervision (ATS), it proposed a calculation scheme of recommended speed curve based on accurate running time. In the scheme, an ant colony algorithm is used, and the difference between actual time and pre-set time is taken as the limited condition. Meanwhile, energy consumption and comfort are also considered. ATO system controls the train according to that speed curve, so the train can reach the destination on the time given by the ATS. Through a large number of tests for the algorithm, the result of the time difference can be within 160 ms. Simulation results show that the train arrives at the next station on time, and the difference of time is less than 1 s compared with the setting time.